PATTERN OF SELF MEDICATION AND DRUGS USE BEHAVIOR AMONG UNDERGRADUATE STUDENTS OF MEDICAL AND NON MEDICAL COLLEGES IN A CITY OF NORTH EAST INDIA- A COMPARATIVE STUDY - Dutta, Sarmistha; HAZARIKA, KAPIL (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective- The present study was undertaken to assess and compare the practice of self medication and drug use behavior among undergraduate students of medical and non-medical colleges in a city in North-East India. Method- A cross sectional questionnaire based study was conducted among 300 undergraduate students each of medical and non medical colleges of Guwahati city of Assam after taking informed consent . Approval of Institutional Ethical Committee was taken prior to the commencement of the study. Data was collected with a prevalidated questionnaire related to various aspects like class of drugs used for self medication, conditions for which self medication may be employed and their knowledge, attitude and practice of self medication etc. Statistical analysis of the data was done. Result- In our study,71% of medical students and 63% of non medical students practiced self medication which was statistically significant. The most common drugs for self medication were analgesics and anti pyretics. Both medical and non medical students considered non severity of illnesses and quick relief from symptoms as the major reasons for self medication. The major information source for most of medical students who practiced self-medication were textbooks and package inserts. Medical students prefer Allopathic system of medicine and Non medical students are more inclined towards Ayurvedic system. Conclusion- Practice, Knowledge and Awareness about self medication is significantly more in medical students in comparison to non medical students which can be attributed to their medical knowledge. Keywords- Self medication, Questionnaire, Package inserts, Allopathic, Awareness, Pharmacy.